Science Process Skills of Undergraduate Biology Students Across Varied Online Practicum Formats: A Quantitative Descriptive Study - Tauhidah, Dian; Astutik, Fuji; Wijayanti, Erna (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2026)
Laboratory practice plays a central role in science education by fostering science process skills (SPS) required for scientific inquiry. During the COVID-19 pandemic, laboratory instruction shifted to online formats, raising questions about the effectiveness of different delivery modes in supporting SPS development. This study analyzed and compared SPS achievement among undergraduate students in Biology Education enrolled in three online laboratory formats at UIN Walisongo Semarang. Using a quantitative descriptive design, 83 students were purposively selected. SPS were measured using a validated 14-item multiple-choice instrument covering nine indicators, supported by observation sheets and semi-structured interviews. Data were analyzed using triangulation, descriptive statistics, and the Kruskal–Wallis H test. The findings showed that Class B achieved the highest mean SPS score (82.02), followed by Class C (79.59) and Class A (66.67), with significant differences among classes (p = 0.020). Varied project-based assignments were more effective in promoting SPS in online laboratory learning. Keterampilan Proses Sains Mahasiswa S1 Biologi pada Berbagai Format Praktikum Daring: Sebuah Studi Deskriptif Kuantitatif ABSTRAK: Praktikum laboratorium memegang peran penting dalam pendidikan sains karena mengembangkan keterampilan proses sains (KPS) yang dibutuhkan dalam inkuiri ilmiah. Selama pandemi COVID-19, pelaksanaan praktikum beralih ke format daring, sehingga memunculkan pertanyaan mengenai efektivitas berbagai mode pembelajaran dalam mendukung pengembangan KPS. Penelitian ini bertujuan menganalisis dan membandingkan pencapaian KPS mahasiswa Pendidikan Biologi yang mengikuti tiga format praktikum daring di UIN Walisongo Semarang. Penelitian menggunakan desain deskriptif kuantitatif dengan melibatkan 83 mahasiswa yang dipilih melalui purposive sampling. KPS diukur menggunakan instrumen pilihan ganda tervalidasi sebanyak 14 butir yang mencakup sembilan indikator, didukung lembar observasi dan wawancara semi-terstruktur. Data dianalisis menggunakan triangulasi, statistik deskriptif, dan uji Kruskal-Wallis H. Hasil penelitian menunjukkan bahwa Kelas B memperoleh skor rata-rata KPS tertinggi (82,02), diikuti Kelas C (79,59) dan Kelas A (66,67), dengan perbedaan yang signifikan antarkelas (p = 0,020). Penugasan berbasis proyek yang bervariasi terbukti lebih efektif dalam meningkatkan KPS pada praktikum biologi daring.